2019
DOI: 10.3892/etm.2019.7228
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of the mRNA expression of members of the HSP90 family in non‑small cell lung cancer

Abstract: The aim of the present study was to investigate the potential prognostic value of members of the heat shock protein (HSP)90 family in non-small cell lung cancer (NSCLC) patients. The mRNA expression profiles of 1,926 NSCLC patients, which was available from the Kaplan-Meier plotter database, were included in the study. High expression of HSP90AA1 mRNA was significantly associated with a poorer rate of overall survival (OS) for all NSCLC patients [hazard ratio (HR), 1.21; 95% confidence interval (CI): 1.06–1.37… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 44 publications
(35 reference statements)
1
21
0
Order By: Relevance
“…The enhancement of tumor suppressing function of ACVR1B might be one possible strategy for treating high-risk LUAD patients. On the other hand, HSP90AB1 overexpression was found associated with poor prognosis both in our study and other studies [36,37]. Whether inhibiting such expression could improve current standard therapies for higher-risk subgroup might warrants further studies.…”
Section: Discussionsupporting
confidence: 67%
“…The enhancement of tumor suppressing function of ACVR1B might be one possible strategy for treating high-risk LUAD patients. On the other hand, HSP90AB1 overexpression was found associated with poor prognosis both in our study and other studies [36,37]. Whether inhibiting such expression could improve current standard therapies for higher-risk subgroup might warrants further studies.…”
Section: Discussionsupporting
confidence: 67%
“…Xu et al reported that MiR-199b-5p can promote tumor proliferation through regulating KLK10 in cervical cancer [35]. Liu et al reported that Heat Shock Protein 90 Beta Family Member 1 (HSP90B1) is significantly related with worse overall survival in lung cancer [36]. Cawthorn et al reported that up-regulated HSP90B1 is related with distant metastasis [37].…”
Section: Discussionmentioning
confidence: 99%
“…Microarray technology has been widely applied in the examination of general genetic abnormalities (1113). Furthermore, the Gene Expression Omnibus (GEO) database is increasingly recognized by researchers with an increasing interest in data mining and bioinformatics and a number of tumor-associated genes, including for NPC, being discovered (14,15).…”
Section: Introductionmentioning
confidence: 99%